2022
DOI: 10.3390/w14233850
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Measures for Protecting the Go-Cong Coastlines (Vietnam) from Erosion

Abstract: Every year, in the Vietnam Mekong Delta Coastal Zone (VMDCZ), erosions cause approximately 300 ha of agricultural land loss. Therefore, measures for shoreline protection are urgently needed. This paper discusses the impacts of protection measures in the Go-Cong Coastal Zone to prevent erosion/accretion processes, predicted by two numerical models, MIKE21-FM and TELEMAC-2D. Hard and soft measures have been proposed using breakwaters and sandbars, respectively. The simulations show that the erosion/accretion tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The findings indicated that fine-grained sediment accumulated as US in the first stage of the morphological evolution of Ngang Island. The sediment accumulation that occurred was partly due to the area experiencing low-energy activities, as previously reported [60,[66][67][68][69]. Sediment accumulation increased steadily and subsequently expanded the shoreline, as shown in Figures 3 and 4.…”
Section: Morphological Evolution Of Ngang Island and Mangrove Growthsupporting
confidence: 73%
See 3 more Smart Citations
“…The findings indicated that fine-grained sediment accumulated as US in the first stage of the morphological evolution of Ngang Island. The sediment accumulation that occurred was partly due to the area experiencing low-energy activities, as previously reported [60,[66][67][68][69]. Sediment accumulation increased steadily and subsequently expanded the shoreline, as shown in Figures 3 and 4.…”
Section: Morphological Evolution Of Ngang Island and Mangrove Growthsupporting
confidence: 73%
“…Currently, the planting of mangrove plants has been prioritized by the existing coastal erosion control measures (for example, ecological engineering—mangrove planting—and engineered solutions for the construction of shoreline and offshore protection structures) to establish intertidal mudflats and stabilize eroded coastal areas in Southeast Asia [ 63 , 64 , 65 ], including Vietnam [ 48 , 66 , 67 , 68 , 69 ]. However, the opposite is true, as shown in Figure 3 , Figure 4 and Figure 6 (1) of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations